Evidence of formation of an amorphous magnesium silicate (AMS) phase during alkali activation of (Na-Mg) aluminosilicate glasses. (July 2021) - Sreenivasan, Harisankar; Adesanya, Elijah; Niu, He; Perumal, Priyadharshini; Kantola, Anu M.; Telkki, Ville-Veikko; Huttula, Marko; Cao, Wei; Provis, John L.; Illikainen, Mirja; Kinnunen, Paivo
Abstract: There is some ambiguity regarding the fate of Mg during the alkali activation of Mg-rich precursors within the broader field of alkali activated materials (AAMs). The present work addresses this issue by studying the reaction products in AAMs synthesized from (Na-Mg) aluminosilicate glasses. Here, instead of magnesium silicate hydrate (M-S-H) phase, Mg exclusively forms an amorphous magnesium silicate (AMS) phase. Compared to M-S-H, AMS is a more depolymerized phase, which has not previously been well documented. The formation of AMS seems to be driven by the high charge density of the Mg cation which effectively stabilizes the depolymerized silicate species. We also show that the lack of hydrotalcite-group phases is due to aluminum depletion by zeolite formation. This work highlights the need to consider the existence of the AMS phase in Mg-containing AAMs, especially in complex systems, where its identification may be difficult. Graphical abstract: Unlabelled Image Highlights: No hydrotalcite-group phase is formed as Al preferentially incorporates into zeolites. Mg forms an amorphous Mg silicate (AMS) phase. AMS is a more depolymerized phase when compared to Mg silicate hydrate (M-S-H). High charge density of Mg effectively stabilizes depolymerized silicates in AMS phase. Existence of AMS phase should be considered as possibility in Mg-rich AAMs.